Preparation of ethylenediamine-modified magnetic chitosan complex for adsorption of uranyl ions - Wang, Jing-song; Peng, Rui-ting; Yang, Jin-hui; Liu, Yao-chi; Hu, Xin-jiang (Carbohydrate polymers, 2011)
Ethylenediamine-modified magnetic chitosan (EMMC) complex was developed as a novel magnetic adsorbent for the removal of uranyl ions. XRD spectrum indicated that the magnetic particles were pure Fe 3O 4 with a spinel structure, and the binding of chitosan did not result in a phase change. IR analysis demonstrated that Fe 3O 4 particles were successfully bounded by chitosan and more amino groups appeared in the EMMC samples. EMMC was found to be quite efficient to adsorb uranyl ions at pH 2–7. Equilibrium was established within 30 min, and the kinetic experimental data properly correlated with the pseudo-second-order kinetic model, indicating that the chemical sorption is the rate-limiting step. The adsorption data could be best interpreted by the Sips model with a maximum adsorption capacity of 82.83 mg U g −1. The EMMC can be regenerated with high efficiency, suggesting that this adsorbent is satisfactory to reuse uranyl ions.